Nonalcoholic fatty liver disease and hepatocellular carcinoma - Klein, Stephanie (Hepat Oncol, 2017)
Hepatocellular carcinoma (HCC) in patients with nonalcoholic fatty liver disease is becoming more common globally. The incidence of HCC due to nonalcoholic steatohepatitis in comparison to other etiologies is increasing. This is due to the pandemic of obesity and diabetes mellitus, two important risk factors for HCC. HCC arising in this context occurs in about 40% of the cases in a liver which is not yet cirrhotic. This has implications regarding the population which should be enrolled in an HCC surveillance program and regarding the treatment options. Surgery is more frequently contemplated in patients with HCC and no cirrhosis. However, patients with nonalcoholic steatohepatitis-induced HCC have frequent co-morbidities which have to be taken into account when developing a management strategy. Interestingly, these patients are frequently on medications which have been suggested to decrease the risk to develop HCC.